Pengembangan E-LKPD PKn Berbasis Proyek Penguatan Profil Pelajar Pancasila (Profil Gotong Royong) di SD - Vivi Nurafifah; Ridho Agung Juwantara; Ambyah Harjanto (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2025)
This study aims to determine the feasibility, educator responses, and student responses to project-based E-LKPD learning media strengthening the Pancasila student profile at SD Negeri 1 Palapa. The research method used is R&D (research and development) and through the ADDIE development procedure which consists of 5 stages, namely: Analysis (anallis), Design (design), Development (development), implementation (implementation), and Evaluation (evaluation) stages. Product validation was carried out by material expert validators who stated that the E-LKPD media product developed obtained a percentage of 95% with the interpretation criteria of “very feasible”, then the results of media expert validation stated that the E-LKPD media product developed obtained a percentage of 97% with the interpretation criteria of “very feasible” and the results of linguist validation stated that the monopoly media product developed obtained a percentage of 77% with the interpretation criteria of “feasible”, While the educator's response obtained a percentage value of 90%, with the interpretation criteria “very interesting”, then the response of students in the small group trial obtained a percentage value of 99%, with the interpretation criteria “very interesting” and in the field trial obtained a percentage value of 97% with the interpretation criteria “very interesting”. The development of project-based E-LKPD PKN media strengthening the Pancasila student profile at SD Negeri 1 Palapa using the research and development (R&D) research method, it can be concluded that the use of project-based E-LKPD media learning media strengthening the Pancasila student profile is very feasible and very interesting to use as learning media.